Monitoring Pembelajaran Konsep Learning By Playing And Playing For Learning Sebagai Peningkatan Kualitas Pendidikan Di TK - Ninik, Ninik (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2018)
Often we do not realize that the age of kindergarten is the age range of play, which at that age they tend to use motoric rough to move to do activities which of course will produce something fun because it can not be separated from the nature of children who tend to play. in the world of education, that the needs of children in this early age they also must learn. And we as adults should realize that children are children, who should When they learn accompanied by a game and when they play unconsciously if they learning. The learning process is essentially the interaction of teachers with students in the context of teaching and learning activities to students to achieve the expected goals. Thus learning to teach must be normative value that contains values ​​that can change the behavior of students. Educational interactive process involves communicative active two-way students and teachers. In this case the child is required to be more active than the teacher in the sense of attitude, mental and action. Teachers act only as facilitators and facilitators, but in preparing the teaching program so that relevance to the characteristics and needs of children of Paud age, teachers can refer to several education experts as well as the development of children. It can be concluded that Learning by Playing & Playing for Learning Theory is very appropriate applied in the institution of kindergarten. Learning while playing and playing while learning is a theory that has a positive influence on the development of students because the world of children is a world of play. Thus enjoyable learning will result in maximum growth and development in the world of education that is expected both in terms of physical motor, language, social emotional, intellectual, and the moral and character of our students.